Broadcasting Umrah through the Hadith of Hajj Badal in the COVID-19 Pandemic Era. - Subkhani Kusuma Dewi; Muhammad Akmaluddin (UIN Sunan Kalijaga Yogyakarta, 2023)
This article delves into an extensive project concerning the development of the umrah industry in Indonesia and its relationship with the interpretation of Hadith. Specifically, it examines the impact of the pandemic on this brief pilgrimage practice in Indonesia, a predominantly Muslim society. Despite the economic setbacks, the pandemic has significantly influenced the widespread use of social media globally. Indonesian Muslims, being active netizens, have shown a strong desire to reconnect with the sacred sites in Mecca and Medina. This article employs a multifaceted approach to investigate the utilization of social media by Indonesian muṭawwifs-vloggers, employing intersecting methodologies. Firstly, it conducts a textual study focusing on thematic badal Umrah. Secondly, it involves (online) observations and participation in the activities of various muṭawwifs vloggers based in Saudi Arabia. The result of this research is that cyber-mediated Umrah experiences cannot fully substitute the physical pilgrimage journey. Badal Umrah, primarily rooted in the badal Hajj Hadiths. It emerges as a crucial practice during times of crises and being used as legitimacy inoffering assistance to those who are physically unable to undertake the journey. Consequently, there has been an increased acceptance of Hadiths related to Hajj and Umrah during the pandemic, .